Pearl Millet Socioeconomic and Production Characteristics in Uganda - Lubadde, Geofrey; Tongoona, Pangirai; Derera, John; Sibiya, Julia (National Semi Arid Resources Research Institute, 2015)
Pearl millet is an important cereal grown by farmers in environmentally marginalised areas. In Uganda it is mainly grown in northern (Acholi), northeastern (Karamoja) and eastern (Teso) regions. The regions are characterised by semi-arid conditions with high temperatures, low mean annual rainfall and widespread chronic food insecurity. Technologies that increase pearl millet productivity under such conditions have been developed in international research institutes to highlight the importance of pearl millet as a resilient crop suitable for drought conditions. However, not much is known about the importance of the crop in Uganda. A baseline survey was thus conducted to document pearl millet farmers’ socioeconomic and production characteristics in the country. Information was collected about demography and food security situation, livelihood, social capital and trainings, importance and utilisation of pearl millet, agronomic characteristics, desirable and undesirable traits, factors of crop and animal production, post-harvest handling, production and marketing constraints and coping strategies. Results indicated that the average age of heads of households (mainly males) was 45.78 years while that of their spouses was 37.22 years; with a pearl millet growing experience of over six years. In addition, majority of the households had 6-10 members many of whom were below 15 years. The heads of households were married with education experience of more than five years while their spouses were generally illiterate. The household heads and their spouses farmed the land as their main economic activity. Furthermore, majority of the households lived under poor conditions where the main house had a single room built of mud and wattle with grass as the main roofing material and earth floor. The poor living standards were worsened by majority of the households facing perpetual food insecurity mainly due to drought, insect pests, plant diseases and lack of improved planting materials.
Keywords: Millet; Production Characteristics